PROSPECTS OF ENGINEER-TECHNICAL ACTIVITY ARE IN THE CONTEXT OF PRAGMATIC PARADIGM OF MODERN SCIENCE - Костюк, О. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is devoted research of prospects of development of engineer-technical activity in the modern world. The question of becoming of ideological principles of modern scientific knowledge opens up.